Avant-garde and after rethinking art now - Taylor, Brandon (New York Harry N. Abrams, Incorporated, 1995)
Introduction: Tradition and Avant-Garde -- 1. Alternatives to Modernism: the 1970s -- A new women's art -- Performance art -- The trials of conceptualism -- The spectre of affirmative painting -- 2. Painting and Politics: 1976-90 -- The return of the figure and of "expression" -- Expressionism contexted -- Something called "post-modernism" -- Painting and "the feminine" -- 3. Stolen Forms: 1976-90 -- Photography and gender -- objects and the market -- Painting and appropriation -- 4. Art within the Museum: the later 1980s -- Culture itself as subject -- Installation as decay -- The curator's part -- The power of the photograph -- A kind of publicity -- 5. Narrating Identity: the early 1990s -- The body and AIDS -- West-coast post-modernism -- Installations and the declasse -- Narrating the body -- The discourse of race -- 6. Coda: Future Prospects.
"Offering a critical perspective-rather than a traditional survey, this provocative text explores the art of the last twenty years-the latter 1970s, the 1980s, and the first half of the 1990s-in both a thematic and chronological fashion. Using an engaging and approachable style-and an abundance of color illustrations, it takes a long look at dominant tendencies in contemporary art in the United States, Western and Eastern Europe, and Russia-and provides a series of challenging view points on the most advanced art forms, themes, and issues." --Amazon.
Includes bibliographical references and index.
Keywords: Postmodernism; Art, Modern -- 20th century; Art and society